PENGARUH EFIKASI DIRI DAN KECERDASAN TINGKAT EMOSI TERHADAP PENGAMBILAN KEPUTUSAN KARIR MAHASISWA TINGKAT AKHIR PROGRAM STUDI ADMNISTRASI UPN “VETERAN” JAWA TIMUR - Maharani Ikaningtyas (Halu Oleo University, 2022)
The current era of globalization also demands progress from all aspects that greatly support the needs of everyday life. One of them is the development of education or education related to this matter which is able to have a positive impact on students. The purpose of this study was to determine how self-efficacy and emotional intelligence affect career decision making for final year students of the UPN